Formative experience and stock price crash risk: Evidence from China’s “Down to the Countryside” movement - Wu, Maoguo; Zhang, Yuang; Shi, Dongkun (Frontiers in Psychology, 2022)
This study explored the influence of chairpersons’ early life experiences during the “Down to the Countryside” movement, a unique social phenomenon in China, on company stock price crash risk. This study used 2007–2018 data from China’s A-share listed companies and a multiple regression analysis model to explore the influence of chairpersons’ Down to the Countryside experiences on the stock price crash risk of their corresponding companies. Propensity score matching, placebo tests, and difference-in-differences tests were conducted to test the findings’ robustness. The empirical results demonstrate that chairpersons’ “sent-down” experiences shape their risk-aversion management style, reducing companies’ risk-bearing capacity. Consequently, this formative experience reduces stock price crash risk and increases company value. Heterogeneity tests on property rights reveal that chairpersons’ sent-down experiences are more pronounced in non-state-owned companies, compared with state-owned companies. These conclusions hold after controlling for a variety of endogeneity issues, such as self-selection bias, and applying a series of endogeneity controls and conducting a robustness check. This study provides a new perspective on the relationship between chairpersons’ early life experiences and stock price crash risk. The empirical evidence has implications for the recruitment, incentivization, and supervision of chairpersons.